Elevskapets utmaningar: Ungdomar, motstånd och önskan om att lyckas i skolan - Andersson, Sara; Lunneblad, Johannes (Educare, 2020)
School segregation has increased in Sweden during the last decades, and students from socio-economically disadvantaged groups ended up in schools with economic challenges as well as overall low goal achievement. The aim of this study is to illuminate how students in urban disadvantaged neighbourhoods relate to school. With an ethnographic approach, the study draws on fieldwork conducted in a junior high school, grade seven, using a combination of theories from Foucault and Goffman as theoretical frame for the analysis. The results indicate that the often described conflict between school and students from disadvantaged groups does not have to always occur. Teachers can use humour and youth culture to prevent the conflict to manifest. However, the central aspect of how students relate to school is the perceived position of disadvantage. Both school achievement and oppositional behaviour against school rules function as ways for students to distance themselves from this position. In conclusion, this study highlights the importance of teachers to counteract the conflict – a form of support – enabling students from disadvantaged groups to succeed in school and thus securing the opportunity for a more prosperous future.